PENGGUNAAN MEDIA GEOBOARD (PAPAN BERPAKU) MELALUI PEMBELAJARAN KOOPERATIF TIPE STAD ( STUDENT TEAM ACHIEVEMENT DIVISIONS) UNTUK MENINGKATKAN PEMAHAMAN KONSEP KELILING DAN LUAS BANGUN DATAR PADA SISWA KELAS IVB MI WAHID HASYIM GONDANGLEGI TP 2017-2018 - Nanik Ulfa (MIDA : Jurnal Pendidikan Dasar Islam, 2019)
Abstract This study aims to improve the understanding of the concept of circumference and the area of flat building using geoboard media (nailed boards) through STAD type cooperative learning. The use of media in this study is expected to help students learn Mathematics. There are three major groups in the Mathematics curriculum, namely planting concepts, understanding concepts and developing skills. Understanding the basic concepts (planting concepts) is the pursuit of a new concept of Mathematics when students have never studied the concept. Understanding of concepts is advanced learning from concepts, which aims to make students better understand a mathematical concept. While coaching skills is advanced learning from planting concepts and understanding concepts. Learning skill development aims to make students more skilled in using various mathematical concepts. The results of this study are known from the average value of students of the first cycle with the average value of students being 68.3, and the number of students completing learning being 56.65%. In the second cycle, the average value of students increased to 77.54 and the number of students completing learning rose again to 82.60%. And from the results of the analysis, it was found that from the first cycle, the correct concept was 50% and in the second cycle, it rose to 75%. From the final test of the second cycle, it showed that students managed to understand the concept of circumference and the area of flat building using geoboard media through STAD type cooperative learning.